2005
DOI: 10.1186/1471-2296-6-20
|View full text |Cite
|
Sign up to set email alerts
|

GPs' perspectives of type 2 diabetes patients' adherence to treatment: A qualitative analysis of barriers and solutions

Abstract: BackgroundThe problem of poor compliance/adherence to prescribed treatments is very complex. Health professionals are rarely being asked how they handle the patient's (poor) therapy compliance/adherence. In this study, we examine explicitly the physicians' expectations of their diabetes patients' compliance/adherence. The objectives of our study were: (1) to elicit problems physicians encounter with type 2 diabetes patients' adherence to treatment recommendations; (2) to search for solutions and (3) to discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
162
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(176 citation statements)
references
References 41 publications
9
162
1
4
Order By: Relevance
“…Previous studies have suggested that individuals with diabetes may not follow recommended guidelines for diet and exercise management [12]. Some studies have found that poor diabetes self-management among diabetes patients led to longterm diabetic complications [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that individuals with diabetes may not follow recommended guidelines for diet and exercise management [12]. Some studies have found that poor diabetes self-management among diabetes patients led to longterm diabetic complications [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…27,[32][33][34][35][36][37][38] Similarly, physicians are often frustrated by patients' difficulties integrating self-care into their lifestyles. [39][40][41] Thus, understanding patients' struggle to achieve treatment goals and physicians' responses to patients who are struggling to integrate selfcare into their lifestyles is important for understanding the physician-patient relationship in type 2 diabetes.…”
mentioning
confidence: 99%
“…19 Therefore, knowing the language of the community, involve family members and integrate them into the educational process is essential in the accession process. 31,32 This stance is intrinsically related to a concern with empathy established for the user, a factor that favors the approach of client health services, contributes to increase their motivation and therefore adherence to diabetes treatment. 33 Beyond Empathy, the host was cited as an important tool in the service and is a determinant in the consequent user satisfaction therefore also associated with a listening RF allows all health professionals to better understand the problems faced by the user, making this pose a mechanism for reasoning guidelines pipeline alternatives that are viable.…”
Section: Strategies Used By Health Professionals Front Of Adherence Tmentioning
confidence: 99%